PENGARUH LATIHAN LADDER DRILL TERHADAP KELINCAHAN PEMAIN SSB BINA MUDA SOMEL - M. Iqbal Chaniago; Ikhsan Maulana Putra; Desi Tri Susanti (CV. Master Literasi Indonesia, 2025)
This study aimed to determine the effect of the Ladder Drill training method on improving the agility of SSB Bina Muda Somel players. Agility is one of the essential physical components in football due to the dynamic and fast-paced nature of the game, which requires players to change direction quickly without losing balance. Movements that involve frequent changes of direction, such as shuttle running, demand alternating contractions in specific muscle groups. This study employed an experimental method with a one-group pretest–posttest design. The subjects consisted of 10 players from SSB Bina Muda Somel. The research instrument used was a 40-meter shuttle run test conducted twice before (pretest) and after (posttest) the training program. The Ladder Drill training was implemented over 10 sessions with systematically structured variations. Data were analyzed using the Kolmogorov–Smirnov test for normality and the paired sample t-test for hypothesis testing, assisted by the SPSS program. The results showed a significant improvement in players’ agility after undergoing the Ladder Drill training. The average pretest score was 6.60, and the posttest average increased to 7.90. The t-value of -8.510 with a significance of 0.000 < 0.05 indicates that Ladder Drill training has a significant positive effect on enhancing the agility of SSB Bina Muda Somel players.